The Effect of Culture Characteristics, Commitment, and Organizational Communication on Employee Performance at Educational Institutions.: Pengaruh Karakteristik Budaya, Komitmen, dan Komunikasi Organisasi terhadap Performa Karyawan Lembaga Pendidikan. - Fikri, Syamsur Rizalul; Ubaidillah, Hasan (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of cultural characteristics, commitment, and organizational communication on the performance of employees of the Independent Cendekia Insan Educational Institution. The analytical tool used is tabulating the questionnaire, collecting data in the form of validity testing and reliability testing. The hypotheses in this study were tested using classical assumption analysis, multiple linear regression, coefficient of determination (R2), partial correlation coefficient, t test, F test and test using SPSS software for Windows version 18. The results of this study resulted in several conclusions, namely: ( 1) There is a simultaneous influence of organizational culture characteristics, Commitment, and Communication on employee performance (2) There is a partial influence of organizational culture, Commitment, and Communication characteristics on managerial performance (3) Among the characteristics of organizational culture, Commitment, and Communication, cultural characteristics organization has the most significant effect on employee performance.